Numerical Simulation of a Flameless Combustion Furnace with Mixtures of Methane and a Sub-Bituminous Pulverized Coal. Issue 9 (2nd September 2017) - Lezcano, Camilo; Obando, Julián; Amell, Andrés
ABSTRACT: A numerical study of flameless combustion with mixtures of methane and a sub-bituminous pulverized coal was carried out. The analyzed mixtures were 0%, 25%, 50%, 75%, and 100% pulverized coal (energy based). The numerical study was performed using the geometry of a laboratory-scale furnace, which was originally designed to obtain the flameless combustion regime burning natural gas. The turbulence was modeled by means of the standard k - model; the interaction between combustion and turbulence was modeled with the eddy dissipation model using a global reaction mechanism for methane. Also, the pulverized coal was modeled as a discrete phase using the Lagrangian approach, where oxidation and gasification reactions were taken into account to model coal consumption. Additionally, all simulations were done keeping the thermal power constant at 28 kW th and the excess air coefficient was fixed at 1.2. It was found that there are no significant changes in the temperature field uniformity when methane is replaced by pulverized coal, and the size of the reaction zone stays quite similar to the case of burning pure methane. Furthermore, for some cases an improvement of the recirculation factor was obtained. Based on the numerical results, it was concluded that it would be possible to obtain a stable flameless combustion regime for the analyzed methane/pulverized coal mixtures.